Africa's Pulse, September 2011 : An Analysis of Issues Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following heading: recent economic trends; and the challenge of employment in Africa: raising the productivity of the informal sector.